2012
DOI: 10.1007/jhep08(2012)134
|View full text |Cite
|
Sign up to set email alerts
|

The quark anti-quark potential and the cusp anomalous dimension from a TBA equation

Abstract: We derive a set of integral equations of the TBA type for the generalized cusp anomalous dimension, or the quark antiquark potential on the three sphere, as a function of the angles. We do this by considering a family of local operators on a Wilson loop with charge L. In the large L limit the problem can be solved in terms of a certain boundary reflection matrix. We determine this reflection matrix by using the symmetries and the boundary crossing equation. The cusp is introduced through a relative rotation be… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
313
0
25

Year Published

2013
2013
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 187 publications
(353 citation statements)
references
References 89 publications
(258 reference statements)
15
313
0
25
Order By: Relevance
“…Clearly, it would be interesting to explore the strong coupling expansions for other examples. Closely related examples are the generalized scaling function, proposed in [49], and the generalized cusp anomalous dimension (or equivalently the quark-antiquark potential), studied in [50][51][52][53][54]. As studied in [33,[55][56][57], the strong coupling analysis of the generalized scaling function is almost in parallel with the cusp anomalous dimension, and thus it is a good exercise to see its resurgent aspect along the line in this paper.…”
Section: Discussionmentioning
confidence: 84%
“…Clearly, it would be interesting to explore the strong coupling expansions for other examples. Closely related examples are the generalized scaling function, proposed in [49], and the generalized cusp anomalous dimension (or equivalently the quark-antiquark potential), studied in [50][51][52][53][54]. As studied in [33,[55][56][57], the strong coupling analysis of the generalized scaling function is almost in parallel with the cusp anomalous dimension, and thus it is a good exercise to see its resurgent aspect along the line in this paper.…”
Section: Discussionmentioning
confidence: 84%
“…(3.61) 16 We also expect the same system of equations to be applicable for β-deformed case and for the integrable observables with boundary (like cusp anomalous dimension [25,26] or DD-brane system [27]). Generalization to these cases can be done through modification of the asymptotic by relaxing power-like behavior at infinity.…”
Section: Asymptotics At Large Umentioning
confidence: 98%
“…25 One should also properly regularise the above sum which is in general divergent. For instance, one can differentiate it a sufficient number of 24 Again, this is very easy to check starting from (4.1).…”
Section: Jhep09(2015)187mentioning
confidence: 99%
“…In [8,18,19] it was shown that the anomalous dimension of the cusped MaldacenaWilson line admits an integrability-based description in terms of an infinite system of integral equations (known as Thermodynamic Bethe Ansatz equations). This anomalous…”
Section: Quantum Spectral Curve For the Quark-anti-quark Potentialmentioning
confidence: 99%